2023
DOI: 10.1002/ehf2.14338
|View full text |Cite
|
Sign up to set email alerts
|

Association between changes in loop diuretic dose and outcomes in acute heart failure

Abstract: Aims Little is known about the association between the starting of or dose changes in loop diuretics during acute heart failure (AHF) hospitalization and post‐discharge outcomes. We investigated the clinical impact of starting loop diuretics and changing the loop diuretics dose during hospitalization on post‐discharge outcomes. Methods and results From the Kyoto Congestive Heart Failure registry, 3665 consecutive patients hospitalized for HF and discharged alive were included in this study. We analysed 1906 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…DeVore and colleagues 13 analysed the impact on the prognosis of loop diuretic dose adjustments after hospitalization, showing no changes in the composite outcome of 30 day mortality or hospitalization. A recent Japanese study conducted by Seko et al 14 confirmed no difference in terms of mortality when comparing patients in whom a decreased dose of loop diuretics was prescribed at discharge with patients in whom the same dose was maintained. Some factors seem to influence the decision of the physicians on the choice of the diuretic strategy at discharge.…”
Section: Down-titration and Prognosismentioning
confidence: 95%
“…DeVore and colleagues 13 analysed the impact on the prognosis of loop diuretic dose adjustments after hospitalization, showing no changes in the composite outcome of 30 day mortality or hospitalization. A recent Japanese study conducted by Seko et al 14 confirmed no difference in terms of mortality when comparing patients in whom a decreased dose of loop diuretics was prescribed at discharge with patients in whom the same dose was maintained. Some factors seem to influence the decision of the physicians on the choice of the diuretic strategy at discharge.…”
Section: Down-titration and Prognosismentioning
confidence: 95%
“…The diuretic response is also highly related to the neurohormonal drive, which can also identify patients with more disrupted pathophysiology and worse outcomes 9–11 . Several studies have demonstrated the association between the dose of diuretics and the outcomes, but this has never been demonstrated in a casual‐effect manner as most of the data come from retrospective analyses or registries 12,13 . Unfortunately, at the moment, we lack objective measures that allow us to adjust the loop diuretic doses in HF patients.…”
mentioning
confidence: 99%
“… 9 , 10 , 11 Several studies have demonstrated the association between the dose of diuretics and the outcomes, but this has never been demonstrated in a casual‐effect manner as most of the data come from retrospective analyses or registries. 12 , 13 Unfortunately, at the moment, we lack objective measures that allow us to adjust the loop diuretic doses in HF patients. Thus, all dose modifications (up‐ and down‐titrations) are made based on the physician's subjective decisions, which can also lead to some bias.…”
mentioning
confidence: 99%